IMPLEMENTATION OF STATISTICAL PROCESS CONTROL (SPC) FOR MANUFACTURING PERFORMANCE IMPROVEMENT (Journal of Mechanical Engineering, 2009)
This paper intends to combine the Hourly Data System (HDS) and Statistical Process Control (SPC) practices to improve manufacturing performances in manufacturing companies. The focus of this work is to find out the frequencies and time duration of machine breakdowns as well as the major causes of breakdowns affecting productivity. Total quality management (TQM) was introduced to improve continually the products or services to increase the customer satisfaction level. SPC is an important tool of TQM. Again HDS is the real time view of production floor of any manufacturing industry. In usual practice, SPC is used as quality control tool. However in this research SPC is used to increase total output identifying major loss times from various machine breakdowns using HDS. Successful implementation of the recommendations of this paper can significantly improve the manufacturing performance of a manufacturing environment. Keywords: Total Quality management (TQM), Statistical Process Control (SPC), Hourly Data System (HDS)   doi: 10.3329/jme.v40i1.3466 Journal of Mechanical Engineering, Vol. ME40, No. 1, June 2009 15-21